Curriculum Implementation in Teaching Strategies: Enhancing Creativity within Secondary Mathematics Classrooms - Sharma Gyawali, Bishnu; Gnawali, Yagya Prasad; Dhakal, Narayan Prasad (Madhyabindu Journal, 2026)
The predominance of teacher-centered instruction constrains the integration of creative approaches in secondary mathematics classroom practices. The main aim of the study was to enhance innovative strategies in mathematics teaching for enhancing creativity gradually multifaceted and active in mathematics classroom practices through curriculum implementation. To achieve the main aim, a qualitative particularly, the narrative inquiry, was applied to explore how innovative teaching strategies affect the 21st century competencies in secondary level. the data were collected through in-depth interviews, from six students (two each school), three mathematics teachers from three community schools (one teacher from each school) and one curriculum expert. The results revealed that continuing classroom practices remain traditional, teacher- centered and rote- learning oriented, relying on paper-pencil approaches. The required policies employed to improve creative work, innovative performance, and critical thinking to provide hands on experiences weak and inadequately emphasized. The study indorses the traditional strategies and prescribed curricula must be updated to enhance 21st century skills in the learners.